Debates sobre o ensino da matemática na década de 1930 - Rocha, José Lourenço (Revista Brasileira de História da Educação, 2012)
O propósito deste trabalho é situar o debate sobre o ensino da matemática do curso secundário, travado na década de 1930, no contexto histórico no qual ele ocorreu, ressaltando-se a importância dada à conquista do controle da política educacional brasileira pelos grupos que disputavam o poder na época. Assim, pretende-se dar uma visão de como as discussões sobre os rumos da educação nacional reproduziram-se no âmbito específico de uma disciplina, no caso, a matemática. Abstract The intention of this work is to point out the debate on the education of the Mathematics of the secondary schools, which occurred in the 1930s, in the historical context in which it occurred, ahead of the importance given to the conquest of the control of the Brazilian educational politics, for the groups that disputed the power at the time. Thus, it is intended to give a vision of as the quarrels on the routes of national education was propagated in the specific scope of one discipline, in the case, Mathematics. Keywords Mathematics Teaching; The History of Mathematics Teaching; The History of Brazilian Education